Materials in the Perspective of Ibnu Sina - Surianto Surianto; Ahmad Asrin; Amroeni Drajat; Salminawati Salminawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze a Materials in the Perspective of Ibnu Sina. This study used qualitative research. The result of this study shows that Materials defined according to the Indonesian Dictionary are materials used to make other materials. Whereas matter is an object. Materialism is an understanding that glorifies material things. Philosophically, matter is the basis of reality. Without material, ideas will not arise.The characteristics of the material is that it has breadth, meaning that it is not just an idea, there is a follow-up. There is real action that can be seen, touched, or felt. Matter has space and time. Matter has shape and form. The material existed before the idea emerged. Because the idea's place is in the material. So that the creation of the material first, then the idea.